Biventricular repair of pulmonary atresia with intact ventricular septum and severely hypoplastic right ventricle: a case report of a minimum intervention surgical approach. Issue 1 (December 2016) - Hata, Hiroaki; Sumitomo, Naokata; Ayusawa, Mamoru; Shiono, Motomi
Abstract Background In patients who have pulmonary atresia with an intact ventricular septum and severe right ventricular hypoplasia, biventricular repair is considered to be impossible and multiple interventions are generally required for definitive repair. Case presentation An initial palliative procedure was performed in a 1-month-old boy to promote right ventricular development by pulmonary valvectomy without disrupting the annulus, and appropriate oxygenation was achieved with a central funnel shunt. The retained annulus caused functional stenosis and prevented unfavorable right ventricular dilatation due to regurgitation. Thirteen years later, without any other intervention, reconstruction of the right ventricular outflow tract was successfully performed for definitive biventricular repair by using a new expanded polytetrafluoroethylene bulging valved conduit with extended longevity. Conclusions The successful outcome in this case suggests that our minimal palliation strategy could be one option for management of these patients.